2023
DOI: 10.3390/ani13040744
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future of Naturally Occurring Antimicrobials Related to Snake Venoms

Abstract: This review focuses on proteins and peptides with antimicrobial activity because these biopolymers can be useful in the fight against infectious diseases and to overcome the critical problem of microbial resistance to antibiotics. In fact, snakes show the highest diversification among reptiles, surviving in various environments; their innate immunity is similar to mammals and the response of their plasma to bacteria and fungi has been explored mainly in ecological studies. Snake venoms are a rich source of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 220 publications
0
6
0
Order By: Relevance
“…A report commissioned by the UK government noted that roughly 700,000 people die annually from infections caused by MDR and XDR bacteria, a figure projected to increase to 10 million deaths per year by 2050 [ 21 ]. Consequently, new antimicrobials are desperately needed, and natural products, such as compounds from plants [ 39 , 40 ], amphibian skin secretions [ 41 ], and snake venoms [ 42 ], represent a potentially underutilized resource in this regard. This study has identified a peptide present in scorpion venom (TtAP-1) with high potency against a range of clinically relevant Gram-positive and Gram-negative bacteria including ESKAPE pathogens ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A report commissioned by the UK government noted that roughly 700,000 people die annually from infections caused by MDR and XDR bacteria, a figure projected to increase to 10 million deaths per year by 2050 [ 21 ]. Consequently, new antimicrobials are desperately needed, and natural products, such as compounds from plants [ 39 , 40 ], amphibian skin secretions [ 41 ], and snake venoms [ 42 ], represent a potentially underutilized resource in this regard. This study has identified a peptide present in scorpion venom (TtAP-1) with high potency against a range of clinically relevant Gram-positive and Gram-negative bacteria including ESKAPE pathogens ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…One previous work reported some selective dose-dependent antimicrobial activities of omwaprin, a WAP isolated from Oxyuranus microlepidotus , through membrane disruption mechanisms [ 224 ]. On the other hand, previously reported nawaprin does not show any antibacterial activity nor does it act as protease inhibitor, a role that whey acidic proteins usually fill [ 223 , 225 ]. Limited information about WAP’s physiological functions and potential biomedical applications may warrant further research.…”
Section: Venom Constituents and Biomedical Applicationsmentioning
confidence: 99%
“…Animal venoms are a complex mixture that contains many proteins, enzymes, peptides, and small molecules [ 86 , 87 ]. Depending on the taxonomic group, the toxins present in venoms have different modes of action and can be used for defense against predators and pathogens in the environment [ 88 , 89 , 90 ]. It is known that animal venoms have a range of molecules with antimicrobial properties, thus making them an important resource for the investigation of compounds with antimalarial potential [ 90 ].…”
Section: Antiplasmodial Toxinsmentioning
confidence: 99%
“…It is a drug used to control blood pressure whose active ingredient was isolated from the venom of the snake Bothrops jararaca [ 102 ]. It is known that several species present toxins that are mainly derived from proteins that have antibacterial, antifungal, antiviral and antiparasitic characteristics [ 90 ].…”
Section: Antiplasmodial Toxinsmentioning
confidence: 99%